Visuospatial ability as a predictor of novice performance in ultrasound–guided regional anesthesia - Atif, Shafqat; Ferguson, Eamonn; Thanawala, Vishal; Bedforth, Nigel M.; Hardman, J.G.; McCahon, Robert A. (American Association of Anesthesiologists, 2015)
Background: Visuospatial ability correlates positively with novice performance of simple laparoscopic tasks. The aims of this study were to identify if visuospatial ability could predict technical performance of an ultrasound–guided needle task by novice operators, and to describe how emotional state, intelligence and fear of failure impact on this. Methods: Sixty medical student volunteers enrolled in this observational study. We used an instructional video to standardize training for ultrasound-guided needle advancement in a turkey breast model and assessed volunteers’ performance independently by two assessors using composite error score (CES) and global rating scale (GRS). We assessed their ‘visuospatial ability’ with mental rotation test (MRT), group embedded figures test (GEFT) and Alice Heim group ability (AH4) test. ‘Emotional state’ was judged with UWIST mood adjective checklist (UMACL) and fear of failure, and ‘general cognitive ability’ with numerical reasoning test (NRT-20). Results: High CES scores (high error rate) were associated with low MRT scores (= −0.54; P<0.001). Better GRS scores were associated with better MRT scores (= 0.47; P<0.001). Regarding emotions, GRS scores were low when anxiety levels were high (= −0.35; P= 0.005) and CES scores (errors) were low when individuals reported feeling vigorous and active (= −0.30; P= 0.01). Conclusions: MRT predicts novice performance of an ultrasound-guided needling task on a turkey model, and as a trait measure could be used as a tool to focus training resources on less able individuals. Anxiety adversely affects performance. Both may therefore prove useful in directing targeted training in USGRA.